SISTEM INFORMASI AKUNTANSI FORMAL-KULTURAL: STUDI CRITICAL ACTION RESEARCH - Mulawarman, Aji Dedi; Lamase, Muhammad Fadhir Abdullah Ido; Ananda, Meryana Rizky; Ramadhani, Febrina Nur (Jurnal Akuntansi Kontemporer, 2023)
Research Purpose. This study aims to design an accounting information system by integrating formal structure and cultural system in a book publishing business.Research Methods. The research was conducted with a critical action research approach which includes planning, action, critical observation, and critical reflection and redesign.Research Result and Findings. Based on the research results, the researcher proposes two things in the design of formal information systems, namely: (1) the use of Open Monograph Press (OMP) in the operational process; and (2) rearranging the flowchart according to the OMP-based operational system so that all functions become clearer and do not overlap. The cultural information system is designed based on family values and trust which turns out to have more important contribution than the formal accounting information system.